2016
DOI: 10.18632/oncotarget.10015
|View full text |Cite
|
Sign up to set email alerts
|

PiwiRNA-651 as marker of treatment response and survival in classical Hodgkin lymphoma

Abstract: PiwiRNAs, small non-coding RNAs processed by Piwi proteins, are involved in maintaining genome stability in germline cells. Recently, piwiRNA expression has been identified in some tumors. We have examined the potential reactivation of the Piwi/piwiRNA pathway in classical Hodgkin lymphoma (cHL). We found that Piwi proteins and three selected piwiRNAs, including piR-651, were expressed in cHL patients and cell lines, indicating that the Piwi/piwiRNA pathway is active in cHL. Interestingly, low levels of piR-65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 51 publications
0
38
0
Order By: Relevance
“…These are of ß26-36 nucleotides (nts) in length characterised by a 3-terminal 2´-Omethylation and are now reported in somatic and cancer cells regulating differentiation, development, proliferation, apoptosis, invasiveness, angiogenesis, chemo-resistance and so on besides their germline functions [Bahn et al, 2015;Khurana and Theurkauf, 2010;Xiong et al, 2015;Weng et al, 2018;Firmino et al, 2016]. More specifically, only a few piRNAs such as piR-651, piR-20365, piR-021285, piR-932 and piR-823 have been reported to regulate oncogenesis of various cancers such as breast, pancreas, lung, kidney, colorectal, cervical, head, neck and gastric cancer [Zhang et al, 2013;Li et al, 2016;Cordeiro et al, 2016;Fu et al, 2015;Yin et al, 2017]. These studies revealed that piRNAs are promising small ncRNAs in cancer research for their prognostic, diagnostic and therapeutic potential.…”
Section: Introductionmentioning
confidence: 99%
“…These are of ß26-36 nucleotides (nts) in length characterised by a 3-terminal 2´-Omethylation and are now reported in somatic and cancer cells regulating differentiation, development, proliferation, apoptosis, invasiveness, angiogenesis, chemo-resistance and so on besides their germline functions [Bahn et al, 2015;Khurana and Theurkauf, 2010;Xiong et al, 2015;Weng et al, 2018;Firmino et al, 2016]. More specifically, only a few piRNAs such as piR-651, piR-20365, piR-021285, piR-932 and piR-823 have been reported to regulate oncogenesis of various cancers such as breast, pancreas, lung, kidney, colorectal, cervical, head, neck and gastric cancer [Zhang et al, 2013;Li et al, 2016;Cordeiro et al, 2016;Fu et al, 2015;Yin et al, 2017]. These studies revealed that piRNAs are promising small ncRNAs in cancer research for their prognostic, diagnostic and therapeutic potential.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the combined therapy of doxorubicin and ifosfamide have shown greater efficacy and improved survival rate, but unfortunately this is associated with severe toxicities such as cumulative cardiotoxicity, renal impairment, bladder toxicity, central encephalopathy, and many more . Therefore, there is an urgency to explore new therapeutic strategies like targeted therapies and diagnostic biomarkers possibly by harnessing the potential role of small non‐coding RNAs (ncRNAs) to curb this aggressive early‐metastatic tumor …”
Section: Introductionmentioning
confidence: 99%
“…Further, aberrant expression of piRNAs has been documented in cancers such as breast, pancreas, lung, kidney, colorectal, cervical, head, neck, and gastric cancer . However, only a few piRNAs such as piR‐651, piR‐20365, piR‐021285, piR‐932, and piR‐823 have been intensively explored and validated in different cancers to decipher their role in oncogenesis . Cheng et al reported that the expression of piR‐823 in gastric cancer tissues was significantly lower compared to non‐cancerous tissues and its increased expression inhibited growth of gastric cancer cells .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations